2018
DOI: 10.1080/09546634.2018.1506083
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and small-molecule medications in the management of pyoderma gangrenosum

Abstract: Pyoderma gangrenosum (PG) is an uncommon inflammatory skin disorder characterized by neutrophil dysfunction. There are currently no FDA-approved drugs for the treatment of this disease, and treatment has typically relied on traditional immunosuppressive medications such as prednisone or cyclosporine. The efficacy of biologics in the treatment of other pro-inflammatory conditions such as psoriasis, rheumatoid arthritis, and inflammatory bowel disease is well-documented in the literature. Therefore, the use of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 189 publications
0
51
0
Order By: Relevance
“…This is also evident in PG’s association with other disorders related to neutrophilic dysfunction, such as inflammatory bowel disease (IBD), rheumatoid arthritis (RA), seronegative arthritis, hematologic disorders, and malignancies such as acute myeloid leukemia (AML) 4, 7 . Interleukin-6 (IL-6), a pro-inflammatory cytokine that plays a role in activation and accumulation of neutrophils, has been found to be elevated in PG lesions 8 . Interestingly, some studies have shown PG lesions to be related to defects in adhesion and function of neutrophils, suggesting a multifactorial pathogenesis 7 .…”
Section: Pathophysiologymentioning
confidence: 99%
See 4 more Smart Citations
“…This is also evident in PG’s association with other disorders related to neutrophilic dysfunction, such as inflammatory bowel disease (IBD), rheumatoid arthritis (RA), seronegative arthritis, hematologic disorders, and malignancies such as acute myeloid leukemia (AML) 4, 7 . Interleukin-6 (IL-6), a pro-inflammatory cytokine that plays a role in activation and accumulation of neutrophils, has been found to be elevated in PG lesions 8 . Interestingly, some studies have shown PG lesions to be related to defects in adhesion and function of neutrophils, suggesting a multifactorial pathogenesis 7 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…No TNFα antagonist has been proven to be more efficacious than others in the treatment of PG. Their use has been associated with a decrease in C-reactive protein (CRP), IL-1, IL-6, and immune cell adhesion markers 8 .…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations